TINJAUAN STATUS GIZI SISWA KELAS VII SMP NEGERI 6 SELAT PANJANG - Erwinsah Erwinsah; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, This study reveals concerns about the state of the nutritional status of students in SMPN 6 Selat Panjang, problems that occurred in this study is caused due to a lack of parental, family economics, the attention of the school and school health programs. The problem of the students in the school nutrition, the researchers propose research titled Overview of the nutritional status of students in SMPN 6 Selat Panjang. This type of research is descriptive quantitative research. The population in this study were all students at SMPN 6 Selat Panjang. Sampling is done in this study is Popurposive Sampling. Samples that researchers choose in this study were students of class VII in SMPN 6 Selat Panjang the number of 233 people. Data collection techniques performed with BB / U (Weight / Age) by dividing Weight with Age of samples (raw Median National Center For Health Statistics). Techniques of analysis in this research using descriptive analysis with the calculation of percentages. After analyzing the data variables studied in get the result that the nutritional status are processed through BB / U of the whole class VII students totaling 233 people are who have Good Nutrition 89 people with a percentage of 38.19%, the students who have satatus Nutrition being as much as 57 with the percentage of 24.46%, the students who have less satatus Nutrition 61 with a percentage of 26.18%, while the poor nourishing as many as 26 students with a percentage of 11.15%. The average score of the assessment of the nutritional staus seventh grade students is 58 with a percentage of 24.89%. Therefore, based on the average score of the overall nutritional status of students of SMP Negeri 6 Selat Panjang categorized Less Good.Keywords: Nutritional Status Overview